Trichostatin a Protects Dendritic Cells Against Oxygen-Glucose Deprivation via the SRSF3/PKM2/Glycolytic Pathway - Jiang, Hongyun; Zhang, Siwei; Song, Tongtong; Guan, Xin; Zhang, Ruojin; Chen, Xia (Frontiers in Pharmacology, 2018)
Dendritic cells (DCs) are important to the immune system and are frequently recruited to hypoxic regions, especially during acute myocardial infarction (AMI). Emerging data indicate that histone deacetylase (HDAC) inhibitors possess immunomodulatory functions. We previously showed in a rat model of AMI that the HDAC inhibitor TSA improved tissue repair, and this was accompanied by increased DC infiltration in the infarct region, suggesting an important role of TSA in modulating DC functions. To study the potential modulatory effect of TSA on DCs, we exploited an in vitro model of hypoxia and glucose deprivation. Culturing of DCs in the presence of 200 nM TSA improved DC survival under hypoxia and glucose deprivation. However, on a phenotypic level, TSA induced the expression of the DC co-stimulatory molecules CD80 and CD86, decreased FITC-dextran uptake, and facilitated DC migration. Moreover, TSA altered cytokine secretion by reducing the pro-inflammatory cytokines IL-1β, IL-10, IL-12 and TGF-β. Furthermore, TSA treatment enhanced HIF-1α-dependent glycolytic gene expression and increased pyruvate kinase M2 by upregulating SRSF3. These results suggest that by TSA alters important DC functions under hypoxia and glucose deprivation, and that TSA is critical for DC function by modulating SRSF3-PKM2-dependent glycolytic pathways.